Three essays on corporate finance - Liu, Zhenbin (2012)
Essay One: Does Corporate Social Responsibility Matter? Evidence from New Equity Issues This paper examines the relevance of corporate social responsibility (CSR) from the perspective of new equity issues. Overall, our findings support the theory that CSR affects equity demand; which, in turn, affects equity valuation. First, in support of the hypothesis that equity demand is negatively (positively) affected by CSR concerns (strengths) of the issuer, we find that (1) issuers with greater CSR concerns are more likely to revise downwards the terms (offer price, number of shares offered, and total proceeds raised) of their stock offerings; (2) the probability of the over-allotment option being exercised is negatively related to CSR concerns in SEO issues, but is positively related to CSR strengths in IPO issues; (3) firms with greater CSR strengths (concerns) are more likely to choose fully-marketed offers (accelerated offers); and (4) the change in the percentage of institutional holdings around the issue date is positively (negatively) related to CSR strengths (concerns). Second, on the effects of CSR on equity valuations, we find that (1) IPOs with greater CSR concerns are more likely to be overvalued, while SEOs with greater CSR strengths have higher underpricing; (2) CSR concerns are negatively related to abnormal returns around SEO announcement dates; and (3) SEO firms with high CSR concerns underperform SEO firms with low CSR concerns over both three-year and five-year post-issue periods.